Periodontitis Is Associated With Heart Failure: A Population-Based Study (NHANES III) - Yan, Yan; Mao, Min; Li, Yan-Qin; Chen, Yong-Ji; Yu, He-Dong; Xie, Wen-Zhong; Huang, Qiao; Leng, Wei-Dong; Xiong, Jie (Frontiers in Physiology, 2022)
Objectives: To investigate the relationship between periodontitis and heart failure using the Third National Health and Nutrition Examination Survey (NHANES III). Methods: Participants who had received a periodontal examination were included and investigated for the occurrence of heart failure. The included participants were divided into no/mild periodontitis group and moderate/severe periodontitis group according to their periodontal status. Weighted prevalence of heart failure was calculated and weighted logistic regressions models were used to explore the association between periodontitis and heart failure. Possible influencing factors were then explored through subgroup analysis. Results: Compared with the no/mild periodontitis group, the incidence of heart failure in participants with moderate/severe periodontitis was 5.72 times higher (95%CI: 3.76-8.72, P<0.001). After adjusting for gender, age, race, body mass index, poverty income ratio, education, marital status, smoking status, drinking status, hypertension, diabetes, stroke, and asthma, the results showed that the incidence of heart failure in the moderate/severe group was 3.03 times higher (95%CI: 1.29-7.13, P=0.012). Subgroup analysis shows that male, 40-60 years old, non-Hispanic white, body mass index >30, poverty income ratio ≥ 1, no more than 12 years of education, currently drinking, stroke but no diabetes or asthma supported moderate/severe periodontitis as a risk factor for heart failure (P<0.05). Conclusion: According to data from this nationally representative sample from the United States, periodontitis is associated with an increased risk of heart failure.